ALGORITHMIC SKILLS AND THEIR RELATIONSHIP TO THE EFFICIENCY OF COGNITIVE REPRESENTATION AMONG FIFTH-GRADE STUDENTS IN MATHEMATICS (Intent Research Scientific Journal, 2024)
Current research aims at identifying the relationship between algorithmic skills and the efficiency of cognitive representation of fifth graders in mathematics. The two researchers used the descriptive curriculum (study of relationships and associations), applying the algorithmic skills test and measurement of cognitive representation efficiency, from which the following questions emerge